2018
DOI: 10.1007/s10029-017-1718-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic methodological review of reported perioperative variables, postoperative outcomes and hernia recurrence from randomised controlled trials of elective ventral hernia repair: clear definitions and standardised datasets are needed

Abstract: VH RCTs report peri- and post-operative variables inconsistently, and with poor definitions. A standardised minimum dataset, including definitions of recurrence, is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 75 publications
0
34
0
Order By: Relevance
“…Sixty-seven articles were from the primary literature, comprising 44 case series, 17 case reports, 4 retrospective database analyses [ 18 , 33 35 ], and 2 retrospective interventional studies [ 36 ] [ 30 ]. Ten articles were from the secondary literature comprising seven editorials, two systematic reviews [ 20 , 37 ] and one consensus questionnaire [ 11 ]. The primary literature reported a total of 1528 patients; 419 of these were retrospective database analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-seven articles were from the primary literature, comprising 44 case series, 17 case reports, 4 retrospective database analyses [ 18 , 33 35 ], and 2 retrospective interventional studies [ 36 ] [ 30 ]. Ten articles were from the secondary literature comprising seven editorials, two systematic reviews [ 20 , 37 ] and one consensus questionnaire [ 11 ]. The primary literature reported a total of 1528 patients; 419 of these were retrospective database analyses.…”
Section: Resultsmentioning
confidence: 99%
“…One systematic review of the prospective randomized studies and reviews in the treatment of ventral and incisional hernias found only a limited evidence base for determining the best treatment options for patients despite the large number of patients with ventral and incisional hernias and the high frequency of repair ( 28 ). Another analysis of the literature on elective surgery of ventral and incisional hernias identified inconsistencies in reporting of peri- and postoperative variables and poor definition of variables ( 29 ). A further problem is the pooling of primary ventral hernias and incisional hernias in many studies, meta-analyses and systematic reviews ( 30 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…This threshold can be summed up in a grip factor characterizing each individual reconstruction [ 8 ]. Due to high recurrence rates and rising socioeconomic cost, ventral hernia repair requires better standardization [ 1 ]. Considering biomechanical stability as a prerequisite for a stable scar formation there is a need for mechanical testing of reconstructions [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the Kruskal-Wallis-test, the necessary increase is statistically significant (p = 0.00042). Most randomized controlled studies quote hernia dimensions as an inclusion criteria but fail to report the mesh sizes used in relation to the hernia size [ 1 ]. Hernia overlap not tailored to the diameter of the hernia orifice is recognized as a key determinant of hernia recurrence [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation